Gerakan Pembersihan Pantai Untuk Mengurangi Sampah Di Kawasan Pantai Pulau Pigago Pasaman Barat - Lutfiyani, Lutfiyani; Fitria, Mita; Septiana, Yuda Dina; Kurnia, Ridho; Yenni, Yenni; Hamdan, Hamdan (Abdimas Indonesian Journal, 2024)
Garbage and environmental pollution are one of the problems faced in the coastal area of ​​Pigago Island, which is located in West Pasaman Regency. One solution to deal with this problem is to encourage people to be more aware of the dangers of rubbish by socializing and carrying out rubbish cleaning activities around the beach area. The activity carried out was to clean the beach in the Pigago Island area. This service method combines theory and practice. In the theory section, material is presented through a presentation followed by a question and answer session to clarify understanding. Meanwhile, in the practical part, participants participate directly in beach cleaning activities by cleaning up rubbish in the beach area. This activity was attended by as many as 120 participants consisting of lecturers and students from STAI YAPTIP West Pasaman. This activity was carried out well and smoothly according to plans and objectives. This activity began by coordinating with the local government and then continued with cleaning the surrounding beaches. Apart from that, this activity also aims to increase the attractiveness of tourists so that they are more interested in visiting.